2005
DOI: 10.1111/j.1525-1438.2005.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated serum antigen level: a novel prognostic indicator for survival in patients with recurrent ovarian carcinoma

Abstract: The aim was to examine the value of the pretherapeutic serum cancer-associated serum antigen (CASA) level as a prognostic factor for survival in patients with recurrent epithelial ovarian carcinoma. Serum levels of CASA and cancer antigen (CA)125 were prospectively determined in 70 consecutive patients with recurrent ovarian cancer before the start of second-line chemotherapy. Univariate and multivariate analyses of survival were performed. The median level of serum CASA was 6.5 U/mL (range: 0.2-1437 U/mL). Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The finding of CASA as a chemoresistance predictor in the present study might be explained by the presumption that ovarian cancer cells overexpressing CASA are more resistant to the effects of inflammatory cells and cytokines in the tumor microenvironment, but this hypothesis should be validated. In comparison, the median level of CASA in the present study (6.8 U/mL) is similar to that found in other series of patients with recurrent ovarian cancer (median 6.5 U/mL) (38).…”
Section: Discussionsupporting
confidence: 92%
“…The finding of CASA as a chemoresistance predictor in the present study might be explained by the presumption that ovarian cancer cells overexpressing CASA are more resistant to the effects of inflammatory cells and cytokines in the tumor microenvironment, but this hypothesis should be validated. In comparison, the median level of CASA in the present study (6.8 U/mL) is similar to that found in other series of patients with recurrent ovarian cancer (median 6.5 U/mL) (38).…”
Section: Discussionsupporting
confidence: 92%
“…Another prospective study examined the value of pretherapeutic CA125 in 70 consecutive patients with recurrent ovarian cancer before the start of second-line chemotherapy. CA125 was not found to be significantly associated with survival by any of the cutoffs (35, 65, 132, and 339 U/mL) [ 39 ].…”
Section: Epidemiologic Studies On Ca125 and Ovarian Cancer Survivalmentioning
confidence: 99%
“…Of the eight studies reviewed under the relationship between prechemotherapy absolute serum CA125 levels and survival, four were prospective, one retrospective, one convenience sample, one consecutive case series type of study. Six studies [ 37 , 38 , 40 - 43 ] showed a highly significant relationship between prechemotherapy serum CA125 level changes and survival whereas one study [ 39 ] did not find such relationship. In one study, prechemotherapy CA125 was found to be strongly correlated with the probability of progression within 3 years but the data suggesting the relationship between prechemotherapy CA125 levels and survival was not provided [ 44 ].…”
Section: Epidemiologic Studies On Ca125 and Ovarian Cancer Survivalmentioning
confidence: 99%
“…CA-125 is a tumor marker of ovarian cancer that plays a significant role in making clinical decisions. Many studies assessed the importance of a single CA-125 measurement [7][8][9][10][11][12][13], while number of studies that analyzed the multiple evaluation of this marker is limited. Conducting such studies is challenging, as they long term follow up, large number of variables and due to difficulties in interpretation of the data.…”
Section: Discussionmentioning
confidence: 99%